Cardiovascular effects of dexamethasone in the preterm infant. Issue 1 (January 1994) - Evans, N
Abstract : Twenty preterm infants were studied serially with Doppler echocardiography to document changes in pulmonary artery pressure, myocardial thickness, and patent ductus arteriosus associated with dexamethasone treatment for chronic lung disease. Pulmonary artery pressure was assessed with Doppler, by its inverse correlation with the ratio of the pulmonary artery time to peak velocity (TPV) and right ventricular ejection time (RVET). Eleven of the 20 infants showed an increase in TPV/RVET after commencing steroids, suggesting a fall in pulmonary artery pressure. This change was not sustained in most cases and had no correlation with the improvement in respiratory status. Ventricular septal and left ventricular posterior wall thickness increased in all 11 infants in whom it was measured. The median increase was respectively 0.9 and 0.8 mm. In most infants this increase was small, less than 1 mm, however two infants developed marked septal hypertrophy with Doppler evidence of left ventricular outflow tract obstruction. Dexamethasone had no consistent closing effect on a patent ductus arteriosus in four infants. Myocardial hypertrophy occurs in most infants, in some it is severe. It would seem prudent to monitor echocardiographically for this side effect.